Design and implement elective module on yoga and yoga-based research in physiology - Wagh, Purushottam; Mahajan, Neeraj; Kumar, Sanjay; Satyanath Reddy Kodidala (Asian Journal of Medical Sciences, 2023)
Background: Elective allows students to think of a career beyond examinations and gives them an impetus to think laterally besides laying down the foundation for future professional pathways. Hence, understanding the importance of electives among medical undergraduates in their academic life is important and electives is not being offered by medical students in India till now. Aims and Objectives: The objectives of this study were as follows: (1) To design elective module on yoga and implement (pilot test) the elective module in 1st MBBS students and (2) to analyze the perception of students and the faculties for the module. Materials and Methods: The study was conducted in the department of physiology among 106 subjects including 1st-year MBBS students and faculty. Faculty sensitization program on the development of the elective module. The evaluation was done by a pre-post standardized validated questionnaire. Perception of faculty (n-05) and students (n-100) taken on Likert’s scale questionnaire by Google form. Results: Results of pre-test and post-test of student’s assessment were compared by paired t-test suggested that outcome is statistically significant with P<0.05 in post-test. Eighty percent of students and 80% of faculties found that the elective module is excellent. Conclusion: The result of the study suggests that the elective module of yoga was well perceived by students and faculty. Electives are learning experiences that will provide the learner with an opportunity to gain an immersive experience of carrier stream, discipline, or research project.